2018
DOI: 10.1111/jphs.12261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist's directed medication reconciliation on reducing medication discrepancies during transition of care in hospital setting

Abstract: Objectives To evaluate the effect of pharmacist's directed services (reconciliation plus counselling) on reducing medication discrepancies and improving patient's outcomes at discharge from hospital. Methods During the 3‐month study period, 200 patients were randomly selected from internal medicine department from Jordan University Hospital (JUH) and allocated into two groups (intervention and control groups). The number and types of medication discrepancies were identified at admission. Then, pharmacist imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 27 publications
(66 reference statements)
0
37
0
Order By: Relevance
“…The outcome denominator was clearly defined in all papers and the data collection method was described clearly in all but one study [91]. The study setting was clearly described in all but six studies [73,80,90,91,93,98]. Validity measures, to assess if independent personnel or an expert panel evaluated the event other than the data collector, were applied in 29 studies […”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome denominator was clearly defined in all papers and the data collection method was described clearly in all but one study [91]. The study setting was clearly described in all but six studies [73,80,90,91,93,98]. Validity measures, to assess if independent personnel or an expert panel evaluated the event other than the data collector, were applied in 29 studies […”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…Three studies [62,64,68] All studies explicitly used the number of discharged patients as their denominator. Across five studies [24,58,64,73,91] that used patients affected by events as their numerator, a median of 27% (IQR 18-40.5) of adult and elderly patients experienced one or more ADRs post-hospital discharge. Two studies [24,73] that used a telephone follow-up as the most common data collection method reported the rate of ADRs post-discharge to be 20.4-27% of discharged patients.…”
Section: Non-preventable Adverse Drug Events (Adverse Drug Reactions)mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] A strong pharmacist-patient relationship is essential to ensure the safe use of drug and prevent the occurrence of drug therapy problems. [9][10][11][12] The pharmacist should provide sufficient to patients about the name of the medication and counsel them about, the frequency and duration of therapy, the route of administration, and the potential toxicities the medication dispensed. 7 Several factors affect the dispensing practice of pharmacists, such as the language barrier, the pharmacists' commitments, knowledge and experience and the dispensing room environment.…”
Section: Introductionmentioning
confidence: 99%
“…12 It was shown that patients had less medication errors when medication reconciliation was performed compared with patients who received standard care. 13,14 Although medication reconciliation has been found to be beneficial in reducing medication discrepancies in both adult and paediatric populations, 12,[15][16][17] however, its success is highly dependent on the ability of healthcare providers to accurately and completely collect a reliable patient medication history at the beginning of the process.…”
mentioning
confidence: 99%